Faktor Penyebab Perceraian Pada Pasangan Usia Subur - Wiqhy Aprilia Ningsy; Surdin; Sitti Kasmiati; La Harudu (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2024)
Divorce of couples of childbearing age in Palarahi village continues to increase. The purpose of this study was to determine the factors that cause divorce in couples of childbearing age in Palarahi Village, Wawotobi District, Konawe Regency. The method used in this research is descriptive qualitative. Data was obtained using observation, interviews, and documentation. Data analysis techniques in this study are data reduction, data presentation, and conclusion drawing/verification. The results showed that: 1) economic factors, basically many families divorce and separate due to economic problems, the inability to meet the needs of life both clothing, food and shelter in the family is what triggers them to divorce, 2) domestic violence, sometimes the husband hits his wife. This is one of the reasons they choose to divorce, 3) Infidelity/adultery, not a few families divorce because of infidelity both husband and wife, 4) disability/health, in this case there is what the husband complains about, namely having had cyst surgery.